Isolation And Identification of Pseudomonas aeruginosa from Some Clinical And Environmental Samples And Study It,s Activity for The Production of Pyocyanin And Protease - Nazar Al-mamari; Adeba Al-Numa,an (College of Education for Pure Sciences, 2019)
The study includes isolation and identification of Pseudomonas aeruginosa from different sources as (90) samples were collected during a period from November (2017) to February (2018), including (wounds, suckers, urine, drinking water), Twinty five isolates of Pseudomonas aeruginosa were identified depending on morphological and biochemical tests at a rate of (27.77%) from total samples including (13) isolates from suckers used for sucking solutions from respiratory tract, (7) isolates from wounds, (3) isolates from urine and (2) isolates from drinking water. The isolates from sucker formed the highest rate reached (14.44%) of total samples and (52%) of total Pseudomonas aeruginosa isolates, whereas the lowest rate was from drinking water (2.22%) of total samples and (8%) of total Pseudomonas aeruginosa isolates. The results showed that (92%) of total isolates were pyocyanin producer on King A agar medium, It was also found that all isolates of this bacteria have the ability to produce protease.